Efficacy and safety of cyclosporine A treatment in autoimmune cytopenias: the experience of two Italian reference centers. (May 2022) - Fattizzo, Bruno; Cantoni, Silvia; Giannotta, Juri Alessandro; Bandiera, Laura; Zavaglia, Rachele; Bortolotti, Marta; Barcellini, Wilma
Background: Immune thrombocytopenia (ITP) and autoimmune hemolytic anemia (AIHA) show good responses to frontline steroids. About two-third of cases relapse and require second-line treatment, including rituximab, mainly effective in AIHA, and thrombopoietin-receptor agonists (TPO-RAs) in ITP, while the use of splenectomy progressively decreased due to concerns for infectious/thrombotic complications. For those failing second line, immunosuppressants may be considered. Objectives: The aim of this study was to evaluate the efficacy of cyclosporine treatment in patients with ITP and AIHA. Design: In this retrospective study, we evaluated the efficacy and safety of cyclosporine A (CyA) in ITP ( N = 29) and AIHA ( N = 10) patients followed at two reference centers in Milan, Italy. Methods: Responses were classified as partial [Hb > 10 or at least 2 g/dl increase from baseline, platelets (PLT) > 30 × 10 9 /l with at least doubling from baseline] and complete (Hb > 12 g/dl or PLT > 100 × 10 9 /l) and evaluated at 3, 6, and 12 months. Treatment emergent adverse events were also registered. Results: The median time from diagnosis to CyA was 35 months (3–293), and patients had required a median of 4 (1–8) previous therapy lines. Median duration of CyA was 28 (2–140) months and responses were achieved in 86% of ITP and 50% of AIHA subjects. Responders could reduce or discontinue concomitant treatment and resolved PLT fluctuations on TPO-RA. CyA was generally well tolerated, and only two serious infectious complications in elderly patients on concomitant steroids suggesting caution in this patient population. Conclusion: CyA may be advisable in ITP, which is not well controlled under TPO-RA, and in AIHA failing rituximab, particularly if ineligible in clinical trial.